New insights into the phenotypic spectrum of 14q22q23 deletions: a case report and literature review - Anna Pichiecchio; Giovanni Vitale; Camilla Caporali; Cecilia Parazzini; Donatella Milani; Maria Paola Recalcati; Laura D'Amico; Sabrina Signorini; Umberto Balottin; Stefano Bastianello (BMC, 2018)
Abstract Background Mutations occurring in the orthodenticle homeobox 2 gene (OTX2) are responsible for a rare genetic syndrome, characterized mainly by microphthalmia/anophthalmia associated with extra-ocular defects such as brain malformations, pituitary abnormalities, short stature and intellectual disability. To date, the spectrum of radiological features observed in patients with OTX2 mutations has never been summarized. Case presentation In this report, we describe a case of large microdeletion encompassing OTX2 but not BMP4 presenting with a syndromic anophthalmia with corpus callosum hypoplasia, pituitary gland hypoplasia and vermian hypoplasia. Conclusion Our case report provides an illustration of the neuroradiological spectrum in a case of OTX2-related syndrome and the first radiological evidence of 14q22.2q23.1 deletion associated posterior cranial fossa anomalies.